Evaluación de dos variedades de arroz (Oryza sativa L.) A la aplicación de diferentes programas nutricionales complementarios a la fertilización Química, en la zona de Babahoyo - Ordoñez Robelli, Jefferson Eduardo (2019)
VIII. SUMMARY The present experimental work was carried out in the CEDEGE Irrigation Project, belonging to the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located on the Babahoyo - Montalvo highway, approximately at km 10.5; between the geographic coordinates 790 32` of longitude West and 010 49` of South latitude; with a height of 8 m.s.n.m. Seeds of rice were used as seed material, Iniap FL 1480 Cristalino varieties, developed by INIAP and Ferón, introduced to the country from Peru. In the trial two treatments were used that were constituted by two varieties of Iniap Cristalino and Ferón rice and four levels of edaphic fertilization with Promet Ca + Promet B + Promet Cu + Promet Zn, in doses of 500 cc + 250 cc + 300 cc + 500 cc; 750 cc + 400 cc + 500 cc + 750 cc; 1000 cc + 600 cc + 700 cc + 1000 cc and Chemical fertilization with N-P - K, according to the nutritional requirement of the crop. The experimental design "Divided Plots" was used with two treatments (rice varieties), four sub-treatments (dose of the nutritional program) and three repetitions. In the evaluated variables, the Tukey test was used. Based on the results obtained, it was determined that the program of chemical Fertilization with N - P - K, according to the nutritional requirement of the crop, flourished in a longer time, which could be attributed to the non - application of the Promet nutritional program; in the agronomic characteristics of plant height, number of tillers and panicles per square meter, length of panicles, grains per panicles and weight of 1000 grains, better averages were obtained in the Iniap Cristalino variety using the Promet Ca + Promet B + Promet Cu program + Promet Zn in doses of 750 cc + 400 cc + 500 cc + 750 cc and the highest yield of the crop was recorded in the Iniap Cristalino variety using the Promet Ca + Promet B + Promet Cu + Promet Zn program in 750 cc + 400 cc + 500 cc + 750 cc with 5554.3 kg / ha, as well as the highest net profit of $ 420.24.